TINDAK PIDANA PENCURIAN DENGAN KEKERASAN YANG MENGAKIBATKAN KORBAN LUKA DI TOKO MAS SIMPANG LIMUN MEDAN (Putusan Nomor 68/id.B/2022/Pn Mdn) - Aryudatama Hasibuan, Dani Sintara (YAPEKAM, 2023)
Rapid developments in this modern era have led to the rise of various criminal acts. At any time may result in this violation. There are no exceptions for theft and aggression. It is not surprising that humans use various methods, including committing crimes, to fulfill the urgent human needs of the nation and state today, considering the increasing demands for life's needs. Based on the problem formulation above, the objectives of this research are: 1. To find out how material criminal law is applied to criminal acts of theft with violence, 2. To find out how the judge considers in handing down decisions against perpetrators of criminal acts of theft with violence in case Number: 68/id.B/2022/PN Mdn, 3. To understand the legal measures taken by criminals in cases of theft with violence. The location for this research was carried out at the Medan District Court Office class 1-A. The type of research used in this research uses two kinds of approaches, namely the normative judicial approach and the empirical judicial approach. The types of data required in this research are primary data and secondary data. Sample distribution is the distribution of the average or primary data and secondary data. Sample distribution is the distribution of the average or proportion of samples taken repeatedly from the population. To obtain correct and accurate data in this research, literature study and field study procedures were carried out. Analysis of data processed from the library is then analyzed descriptively qualitatively. Describe the data descriptively. The conclusion of this research is that law is a series of regulations regarding the behavior of people as members of society, with the aim of establishing safety, happiness and order in society. Based on research results. then the following conclusions can be drawn: 1 the application of the law is in accordance with the applicable material criminal provisions and the conditions for the defendant to be sentenced, this is based on the examination and the facts revealed at the trial, where the evidence submitted by the Public Prosecutor is the testimony of witnesses -Witnesses and evidence are in accordance with the defendant's statement who admits the actions he has committed. So the panel of judges stated that the defendant's actions had fulfilled the elements of the criminal act charged by the Public Prosecutor, namely article 365 paragraph (2) 2e, 4e of the Criminal Code. 2). The judge's legal considerations in handing down a decision regarding the crime of theft with violence in decision Number: 68/id.B/2022/Pn Mdn are appropriate because they are based on descriptions of the statements of witnesses, evidence and the defendant's statement. The judge has also taken into account both judicial and non-judicial considerations which can mitigate or incriminate criminal witnesses for the defendant.